KOMUNIKASI RITUAL TRADISI TUJUH BULANAN (Studi Etnografi Komunikasi Bagi Etnis Jawa Di Desa Pengarungan Kecamatan Torgamba Kabupaten Labuhanbatu Selatan) - Susanti, Elvi; Yohana, Nova (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Tradition Seven Monthly pregnancy is a ceremony for the first child seven months gestation. Seven monthly event is often done by Javanese because this tradition handed down from earlier ancestors. This study aims to determine the implementation of the seven monthly event on Javanese who lived in the Pengarungan village. To achieve these objectives, it raised some questions about how the situation in the event of seven monthly communication, communicative events in seven monthly events, and acts of communication in seven monthly event in the pengarungan village, subdistrict torgamba, labuhanbatu selatan districtThis type of research is qualitative. While research method used is an ethnographic study of communication. Most of the data were collected through observation and interviews. Informants were obtained by 5 people. Three people who existed as a guide Seven Monthly Event and two people who know and understand the events of seven monthly. Data collection techniques by using purposive sampling technique. After the interviews, participant observation, field notes, literature studies, documentation and internet searching. Test the validity of the data with triangulation and the extension of participation.The results obtained indicate that the communicative situation in seven monthly event is done at their own home, or parents' home of the boy and was attended by parents, neighbors, and community members Pengarungan. This communicative events is based on genre, type of events werer, the topic, the purpose and function, the setting, participants, form a message, the content of the message, the rules of interaction, the norms of interpretation. While in communicative acts such as those that know and understand the implementation of seven monthly event is host of the events in seven months.Keywords : Tradition in Seven Monthly Events in the Pengarungan Village,tradition , ethnography of communication